Plot size and shape in trials using strawberry cultivated with soil or using hydroponics - Cocco, Carine; Boligon, Alexandra Augusti; Andriolo, Jerônimo Luis; Oliveira, Clarisse Silva; Lorentz, Leandro Homrich (Pesquisa Agropecuaria Brasileira, 2010)
The objective of this work was to estimate the optimal size and shape of plots to be used in experiments of strawberry (Fragaria x ananassa) cultivation in soil or using hydroponics. Two experiments were conducted, one in soil in low tunnels, and another in a hydroponic system. In each experiment, the effects of plot sizes and shapes on experimental accuracy were evaluated. Each plant was considered an experimental basic unit, and the number of plants per plot varied from 1 (48 plots) to 24 (two plots). Functions were adjusted to determine the coefficient of variation among plots and the variance per basic unit between plots. Plants grown in soil had higher experimental variability than the plants grown in hydroponics. Increasing the number of plants per plot caused strong reduction in the experimental variability, especially when a rectangular plot shape was used. The optimal estimated plot size was ten plants in soil and six plants in the hydroponic system.